2021
DOI: 10.1145/3476077
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Peer Support Needs of Home Care Workers: Emotional Labor & the Politics of Professionalism

Abstract: Home care workers (HCWs) are increasingly central to post-acute and long-term health services in the United States. Despite being a critical component of the day-to-day care of home-dwelling adults, these workers often feel underappreciated and isolated on the job and come from low-income and marginalized backgrounds. Leveraging the support of peers is one potential way to empower HCWs, but peer support encompasses a broad range of activities and aspects. Traditional conceptions of workplace support may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Other, smaller studies include one by Danilovich et al in which a mobile health application was designed to engage HHAs and their patients in physical activity exercises; findings demonstrated that in doing so, HHAs were empowered to expand their training and skills 19 . Additionally, Poon et al found that virtual peer support programs led by trained HHAs offered a safe space for HHAs to build a sense of community, foster empowerment, and mentor one another by collectively sharing their caregiving experiences during the COVID‐19 pandemic 20 . Finally, a qualitative study during COVID‐19 by Tsui et al found that agency‐led phone‐based group support calls with aides improved communication between aides and the agency as well as creating a space in which aides could support each other and feel valued and respected 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Other, smaller studies include one by Danilovich et al in which a mobile health application was designed to engage HHAs and their patients in physical activity exercises; findings demonstrated that in doing so, HHAs were empowered to expand their training and skills 19 . Additionally, Poon et al found that virtual peer support programs led by trained HHAs offered a safe space for HHAs to build a sense of community, foster empowerment, and mentor one another by collectively sharing their caregiving experiences during the COVID‐19 pandemic 20 . Finally, a qualitative study during COVID‐19 by Tsui et al found that agency‐led phone‐based group support calls with aides improved communication between aides and the agency as well as creating a space in which aides could support each other and feel valued and respected 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a physical activity-based training for HHWs by Muramatsu et al (2018) was shown to be well-received by aides and improve their patients’ daily function and physical fitness. 47 Like ours, these studies were single-arm pilot studies composed of unionized and agency-employed aides. Future studies should build on these and test the effectiveness of these disease-specific training courses on not only HHWs but on the self-care and health outcomes of their patients.…”
Section: Discussionmentioning
confidence: 97%
“…New here is that the HHAs offered suggestions of what programs or interventions would work best for them, including support from trained peers. This finding is consistent with a few studies that found peer coach–delivered emotional support programs were feasible and well-received among HHAs before and during COVID-19 . Future studies are underway to formally tailor these programs to the needs of HHAs and evaluate their impact HHAs’ mental health and well-being, delivery of quality care, and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they were asked about their preferences toward future interventions that could meet their needs (eAppendix in Supplement 1). 5,26,27 In addition to the interviews and focus groups, selfreported demographic characteristics, including age, sex, race (including Asian, Black, White, and other [including Hispanic, Brown, or not specified]) and Hispanic or Latinx ethnicity, educational level, and employment history, were collected. Race and ethnicity are essential to include since HHAs are historically a minoritized population (mostly women and women of races and ethnicities other than White) of frontline health care workers; we wanted to ensure that we had diversity in race and ethnicity and by language spoken.…”
Section: Data Collectionmentioning
confidence: 99%